1986
DOI: 10.1111/j.1600-0536.1986.tb01146.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational hand dermatoses in hospital cleaning personnel

Abstract: Hospital cleaning personnel were examined for occupational dermatoses. 356 persons were included in the study. The age ranged from 20 to 63 years with a mean of 40.1 years. The period prevalence rate of moderate and severe eczema was 12% (10% in men and 19% in women). In 88%, the eczema was of a duration longer than 2 years. Positive patch tests were found in 10% of men and 53% of women with eczema. The main allergens were nickel, cobalt, chromate and rubber chemicals. Positive tests to cleaning agents were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 6 publications
1
21
0
1
Order By: Relevance
“…Due to regulations in Spain that protect information that would have allowed us to identify, contact, and collect additional information from individuals who did not participate in this study, (19), our study did not include any additional data collection from non‐responders, and we are not able to draw further conclusions about differences between responders and non‐responders (9). The prevalence of hand dermatitis reported by participants in our study is within the range of those reported among cleaners (5, 8, 20) and general population‐based samples (21, 22), suggesting that, despite the low response rate, the external validity of our data is not markedly compromised. In fact, the enrolment of 818 participants in a research study focused on the health of workers in a large and diverse industry in which investigators and other public health personnel have limited workplace access is a noteworthy strength of our study.…”
Section: Discussionmentioning
confidence: 82%
“…Due to regulations in Spain that protect information that would have allowed us to identify, contact, and collect additional information from individuals who did not participate in this study, (19), our study did not include any additional data collection from non‐responders, and we are not able to draw further conclusions about differences between responders and non‐responders (9). The prevalence of hand dermatitis reported by participants in our study is within the range of those reported among cleaners (5, 8, 20) and general population‐based samples (21, 22), suggesting that, despite the low response rate, the external validity of our data is not markedly compromised. In fact, the enrolment of 818 participants in a research study focused on the health of workers in a large and diverse industry in which investigators and other public health personnel have limited workplace access is a noteworthy strength of our study.…”
Section: Discussionmentioning
confidence: 82%
“…Evaluating the skin safety of the color additive in combination with chlorine disinfectants was a major priority, given the risk of occupational exposure to disinfectants and skin diseases in healthcare personnel. [34][35][36] An independent GLP-compliant facility conducted direct primary skin irritation studies on all 3 chlorine disinfectants with and without color additive and found all to be negligible irritants. Thus, the addition of color additive to chlorine disinfectants does not increase their potential to cause skin irritation.…”
Section: Discussionmentioning
confidence: 99%
“…Among fe male farm er s, the risk for hand dermatoses was more than twofold, and for hand derm atoses without other sites of derm atosis the risk was fou rfold that of the men ' s. The risk for hand derm atiti s was higher for wo men und er 35 yea rs of age than for older women. There are also other studies that sho w higher hand ec ze ma prevalen ces for women than men, and also hig her prevalences for young women (20,26,27) . In addition to domestic wor k and other environmenta l ex posures , constit ution al factor s of wome n may be in vol ved .…”
Section: Discussionmentioning
confidence: 99%